Development of Islamic Religious Education Material Supplements for Handling Verbal Abuse in Elementary Schools - Rizka Setiawan; Joko Subando (South Sulawesi Education Development (SSED), 2024)
The rapid growth of media content and viewing via the internet with the help of smart phones has caused the influence of dependency, a sense of self-existence in cyberspace, disturbed sleep quality, and the emergence of bullying behavior in schools. This study aims to equip students with the skills and quantity of Islamic religious education in the form of teaching modules on handling verbal abuse at the Muhammadiyah Bulu Elementary School. The development research model was created following the ADDIE development steps, but was limited to the development stage. Teaching materials were created using Canva and Microsoft Word software. The product validation results obtained an average of 92% and were classified as very valid. The results of the validation test were used as material for revision and improvement of teaching materials. Teaching materials were tested on Islamic religious teachers and 5th grade students at the Madrasah Ibtidaiyah Muhammadiyah Bulu, with a total of 20 students. In general, the trial results were categorized as very good, with a trial score for teachers of 93% and for students of 95%. Based on the trial results, it can be seen that this teaching material supplement is very good for use in learning. This research only reached the development stage so further research is needed up to the implementation and evaluation stages.